Popularity of the internet with university students - Szpringer, Monika; Laurman-Jarząbek, Edyta; Kosecka, Justyna (Medical Studies/Studia Medyczne, 2014)
Introduction: Virtual reality constitutes an exceptional chance to support personal development, but it also creates new barriers and inequalities and it brings about many threats, both to the person and to society in general. Besides the indubitable advantages of the Internet, it more and more often endangers the harmonious development of a person. Virtual reality puts users in a situation in which interaction and communication is conducted differently to what they are used to based on their everyday experience. Aim of the research: The aim of the research was an analysis of the Internet’s popularity among university students. The method that was used was a diagnostic survey, carried out using questionnaires, which were the tools used to achieve the goal. Chosen results of the research, essential from the point of view of the formulated problem, were presented in the project. The research issue is encapsulated in the question: How popular is the Internet among university students? Material and methods: Empirical research was conducted in the academic year 2010/2011 at universities in the Świętokrzyskie province. A total of 950 students attending medical majors (nursing, physiotherapy, medical rescue), pedagogical majors (social rehabilitation, integrated pre-school and early education, pedagogy with logopaedics) and technical majors (mechatronics, construction) took part in the research. Results: More than 50% of the people that took part in the research were between 20 and 25 years of age. Over 33% of them were aged between 26 and 30. More than 87% of the participants used the Internet, 88% of the respondents had created a Facebook account, 81% of the students logged into the Nasza Klasa website and over 76% of them admitted to frequent use of scientific information found in the Internet. More than 55% of them benefited from psychological counselling via the Internet. In the presented research 75% of the students used the GG (Gadu-Gadu) messenger service very frequently. The conducted study confirmed that over 64% of the polled students used online shops very frequently and more than 73% of the respondents looked for a life partner on a dating website. Seventy-eight percent of the respondents looked for employment in the Internet, the biggest percentage of whom were students of medical majors (85.42%) and pedagogical majors (78.62%). Conclusions : The Internet has become a meta-reality, as important as the real world. The basic space in which the Internet User Generation functions is in the form of social network portals. People more and more willingly create their accounts on more than one social network portal. This is a craving for meeting other people, restoration of contacts from the past and getting to know new cultures (often subcultures).